Comparison of Pain Intensity in Canine Removal Using Closed Coil Spring Niti, Open Coil Spring Niti, Elastomeric Chain Short, Elastomeric Chain Long in Edgewise Standard Fixed Orthodontic Treatment - Oryce Zahara; Endah Mardiati; Nila Kasuma; Fuccy Utamy Syafitri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Every canine is pulled during fixed orthodontic treatment, whether using an elastomeric chain short, elastomeric chain long, closed coil spring, or open coil spring, tends to cause pain for the patient. Which of the four components of the active device is the best in terms of the pain effect felt by the patient. Pain is a symptom that underlies most patients’ rejection of proposed treatment plans. The success of treatment cannot be separated from factors of relief of pain in general, and failure to address these factors may leave patients fearful of returning. This study aimed to compare pain intensity during canine extraction using closed coil spring niTi, open coil spring niTi, elastomeric chain short, and elastomeric chain long in fixed orthodontic treatment standard edgewise. Methods: This study is a longitudinal experimental research. A total of 16 research subjects participated in this study. The data analysis technique for this research is pain intensity analysis based on the time when the canine tooth is retracted using a tool elastomeric chain short, elastomeric chain long, closed coil spring, open coil spring, using the VAS questionnaire on the 1st, 3rd, and 7th days using non-parametric Kruskal Wallis statistical tests to find out whether there are significant differences between 3 different times on 4 different types of equipment. Results: There is no difference in intensity pain after canine retraction using closed coil spring, open coil spring, elastomeric chain short, or elastomeric chain long devices in standard edgewise fixed treatment based on VAS on the 1st, 3rd, and 7th days. There is no difference in intensity pain after canine retraction using a closed coil spring appliance in standard edgewise fixed treatment based on VAS on the 1st, 3rd, and 7th days. There are differences in the intensity of pain after retraction of the canine tooth using an elastomeric chain short, elastomeric chain long appliance in standard edgewise fixed treatment based on VAS on the 1st and 3rd days. Conclusion: There are differences in pain intensity during canine extraction using closed coil spring niTi, open coil spring niTi, elastomeric chain short, and elastomeric chain long in fixed orthodontic treatment standard edgewise.